2017
DOI: 10.1016/j.ijcard.2017.07.068
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac defects, morbidity and mortality in patients affected by RASopathies. CARNET study results

Abstract: The risk of intervention was higher in individuals with Noonan syndrome and pulmonary stenosis carrying PTPN11 mutations. Overall, mortality was relatively low, even though the specific association between HCM, biventricular outflow tract obstructions and PTPN11 mutations appeared to be associated with early mortality, including immediate post-operative events and sudden death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 32 publications
6
64
1
Order By: Relevance
“…Studies suggest that there are higher risks associated with cardiac interventions for patients with NSD as well as higher rates of re-intervention. 10,52 Thus, being able to accurately ascertain individuals at-risk for NSD may be important prior to intervention. Furthermore, guidelines for referral would optimize genetics resource utilization including clinical evaluation and testing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that there are higher risks associated with cardiac interventions for patients with NSD as well as higher rates of re-intervention. 10,52 Thus, being able to accurately ascertain individuals at-risk for NSD may be important prior to intervention. Furthermore, guidelines for referral would optimize genetics resource utilization including clinical evaluation and testing.…”
Section: Introductionmentioning
confidence: 99%
“…In the Pediatric Cardiomyopathy Registry study, three patients with NS and HCM were listed in the follow‐up period, but none survived to transplant . Calcagani et al reported a 7‐year‐old patient with NS who underwent heart transplantation, and died of rejection 8 months after transplantation. Al‐Rahawan et al reported a patient with CFC syndrome who underwent heart transplantation at 8 months of age for HCM with heart failure and outflow obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…HCM is known to be more prevalent among individuals with RAF1‐ , RIT1‐ , HRAS‐, and NSML‐associated PTPN11 mutations, with prevalence as high as 80% in some genotypes . While HCM is relatively rare in children under 1 year of age, HCM related to NS most often presents in the first year of life, being the leading genetic cause of HCM in this age group, and a leading cause of morbidity and mortality among infants and children with NS . Children with NS and HCM also have a less favorable outcome when compared with age‐matched children with idiopathic or familial/sarcomeric forms of HCM, with higher mortality (15% at 3 years compared with 11% in isolated HCM), and greater likelihood of heart failure symptoms at presentation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be related to environmental, infectious and genetic etiologies (Ware, ). CMPs in NS are associated with significant morbidity and mortality, representing a frequent cause of heart failure and mortality, particularly in children and young adults (Calcagni et al, ). Previous reports state that mortality in NS patients is relatively low, but mainly related to severity of cardiac involvement.…”
Section: Introductionmentioning
confidence: 99%